2006
DOI: 10.1007/s11837-006-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation properties of fourth generation single-crystal nickel-based superalloys

Abstract: High-Temperature Applications Research SummaryThe fourth-generation nickel-based single-crystal superalloys, which contain large amounts of refractory metals for strengthening and platinum group metals for topologically close-packed phase prevention, show excellent hightemperature strength. However, these alloying elements seem to decrease high-temperature oxidation resistance. In this study, nickel-based superalloys with various amounts of tantalum, rhenium, and ruthenium were examined in isothermal and cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 15 publications
4
40
0
2
Order By: Relevance
“…It was shown that the volume change ratio / Al 2 O 3 associated with this reaction and defined as: 3 . This fractional volumetric expansion of 0.336 corresponds to a lateral expansion of each c 0 particle of *10%.…”
Section: (A) (B) (D) (C)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the volume change ratio / Al 2 O 3 associated with this reaction and defined as: 3 . This fractional volumetric expansion of 0.336 corresponds to a lateral expansion of each c 0 particle of *10%.…”
Section: (A) (B) (D) (C)mentioning
confidence: 99%
“…They have been optimised for high creep strength and microstructural stability and, with *6 wt% Al and *3 wt% Cr, would be expected to have only a borderline capacity to form and maintain a protective alumina layer [1]. Reported work on the oxidation of these types of alloys tends to be focussed on behaviour at high temperatures, C1,000°C [2][3][4][5][6][7]. At these temperatures, under thermal cycling conditions, non-protective oxides form together with sub-surface oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…800 C [8]), improved phase stability by Ru can all attribute its superiority in creep resistance over previous generations [1,8]. However, higher Ru and Re content in both low Cr bearing TMS-162 and TMS-173 have resulted in poorer oxidation resistance at elevated temperatures due to vaporization of Ru and Re oxides [12], so a much improved oxidation resistance would be required for their practical applications. During oxidation at temperatures above 700 C, scales of Al 2 O 3 , Cr 2 O 3 , NiO, spinel Ni(Cr, Al) 2 O 4 can form on advanced superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…Given the rising turbine entry temperatures sought by engine manufacturers for efficiency gains, oxidation is becoming a more and more prevalent failure mechanism. However, generally fourth generation alloys are significantly poorer in oxidation than second generation alloys such as CMSX-4 [2,3]. It is desirable for intermediate pressure (IP) turbine blades to be uncoated but since the oxidation performance of fourth generation alloys may not be acceptable it is necessary to evaluate simple economically viable coatings, such as aluminides.…”
Section: Introductionmentioning
confidence: 99%